Perception of the activities and image of Ismail Gasprinsky by the Tatar intelligentsia of the early 20th century - Elmira K. Salakhova (Историческая этнология)
The activities of Ismail Gasprinsky including his ideas and practical steps (publication of the Tarjuman newspaper, the beginning of the Muslim school system reorganization) aimed at reforming the education system was a completely new phenomenon in the Turkic-Tatar community. The public reaction to his plans for large-scale reforms was mixed. At first, society treated them with great caution. However, the positive results demonstrated by the shakirds of the new method madrassas and mektebes gradually changed the attitude of society towards the new method and more and more supporters began to think about introducing a new approach to teaching children. The mugallims of Tatar madrassas, who had extensive experience in teaching children using traditional methods, began to look closely at the new educational approach of Ysuly Sautiya. The transition to a new sound method of teaching in Tatar society happened quite quickly and painlessly, the benefits were obvious even to those who doubted it. However, some of Gasprinsky’s ideas, for example, about the common Turkic language, did not find support and approval in Tatar society. The purpose of the publication is to reveal the perception by the Tatar intelligentsia of I. Gasprinsky’s practical activities, ideas and plans at the beginning of the 20th century. The sources for the study were materials from the Tatar periodical press of the early 20th century, individual articles and memoirs of two representatives of the Tatar intelligentsia R. Fakhrutdin and G. Iskhaki. The used materials are written in the Old Tatar language in Arabic script. Therefore, they are inaccessible to a wide range of readers. This study expands the possibilities for reconstructing intellectual discussions in the Turkic-Tatar society of the early 20th century related to the personality of I. Gasprinsky.